The Role of Social Media Da'wah in Improving Individual Piety during the Covid 19 Pandemic - Heni Ani Nuraeni; Novie Kurniasih (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This study aims to analyze the use of social media as a da'wah platform during the covid 19 pandemic. The research is directed at observing the role of social media da'wah in increasing individual piety. This study uses a qualitative approach through descriptive methods. Descriptive research is research whose purpose is to present a complete picture of exploration and clarification of a phenomenon. Data were collected through observation, interviews, and distributing questionnaires via a google form. The subjects in this research are women aged 30-60 years who live in Jakarta and are active social media users. The results show that social media can increase knowledge, sources of information, communication and increase individual piety. The increase in individual piety is marked by the dominance of access to religious content during the COVID-19 pandemic. In addition, religious content that many users access is related to worship, such as prayer, zakat, infak and alms, fasting, hajj, and reading the Qur'an. Individual piety becomes an immunity that strengthens self-confidence and capital in building social piety.